The Effect of Work Discipline and Work Motivation on Employee Performance in a Soap Company - Cahya Eko Susilo,; Suroso,; Flora Patricia Angela,; Uus Mohammad Darul Fadli ,; Azlina Md Yassin, (Research in Management of Technology and Business, 2024)
The aim of this study is to examine how employee performance is affected by both work discipline and motivation as well as to explore the relationship between these two independent variables. The research was conducted at a soap company that produces household chemicals, located in Karawang. The results for this study were based on the quantitative method and includes a population of 142 active employees from the company's LQ3 group B division. Using the Slovin formula with a 5% margin of error, a sample of 103 respondents was selected. Path analysis was used for data processing in this study. The findings indicate a positive relationship between work discipline and work motivation, with a Pearson correlation value of 0.471, categorized as strong. The individual impact of work discipline on employee performance is 0.219, which equates to 21.9%, while the impact of work motivation is 0.121, or 12.1%. When considering both independent variables together, the combined effect on employee performance is 0.494, representing 49.4%, with the remaining 50.6% attributed to other unexamined factors. These results will helps the employer to increase their profits by providing related courses to their employee.